2011
DOI: 10.1002/bdrb.20314
|View full text |Cite
|
Sign up to set email alerts
|

NTP‐CERHR expert panel report on the developmental toxicity of soy infant formula

Abstract: Soy infant formula contains soy protein isolates and is fed to infants as a supplement to or replacement for human milk or cow milk. Soy protein isolates contains estrogenic isoflavones (phytoestrogens) that occur naturally in some legumes, especially soybeans. Phytoestrogens are nonsteroidal, estrogenic compounds. In plants, nearly all phytoestrogens are bound to sugar molecules and these phytoestrogen-sugar complexes are not generally considered hormonally active. Phytoestrogens are found in many food produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
76
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 161 publications
(314 reference statements)
2
76
0
Order By: Relevance
“…Studies evaluating these possible favorable effects have led to conflicting results (Andres et al, 2011;Kwack et al, 2009;Sacks, 2005). Nevertheless, an increased demand for soy and soy-based supplements by consumers has led to a significant rise in the use of soy-derived protein in an array of food products (Kwack et al, 2009;McCarver et al, 2011). This may be of concern as the ingestion of isoflavones has been associated with impaired reproductive function in sheep (Ch'Áng, 1958), mouse (Kaludjerovic et al, 2012), cheetahs in captivity (Setchell et al, 1987), and three women presenting with reproductive pathology (Chandrareddy et al, 2008).…”
mentioning
confidence: 99%
“…Studies evaluating these possible favorable effects have led to conflicting results (Andres et al, 2011;Kwack et al, 2009;Sacks, 2005). Nevertheless, an increased demand for soy and soy-based supplements by consumers has led to a significant rise in the use of soy-derived protein in an array of food products (Kwack et al, 2009;McCarver et al, 2011). This may be of concern as the ingestion of isoflavones has been associated with impaired reproductive function in sheep (Ch'Áng, 1958), mouse (Kaludjerovic et al, 2012), cheetahs in captivity (Setchell et al, 1987), and three women presenting with reproductive pathology (Chandrareddy et al, 2008).…”
mentioning
confidence: 99%
“…Despite these apparent health benefits, the National Toxicology Program recently raised its level of concern about the potential reproductive toxicity of soy infant formula from negligible to minimal (31). This re-evaluation of soy infant formula, which has been in use in the US for over 50 yr and which is consumed by nearly 1 million infants/year, was motivated by a series of in vitro and in vivo results evaluating the estrogenic properties of the soy isoflavone genistein (31).…”
mentioning
confidence: 99%
“…This re-evaluation of soy infant formula, which has been in use in the US for over 50 yr and which is consumed by nearly 1 million infants/year, was motivated by a series of in vitro and in vivo results evaluating the estrogenic properties of the soy isoflavone genistein (31). Although epidemiological studies in human infants consuming soy formula revealed normal growth and development (13,55), there is a concern that infants consuming soy formula are exposed to dangerously high levels of genistein and are at increased risk for reproductive tract malformations and for estrogen-sensitive cancers such as breast and uterine cancer, similarly to children of women exposed to diethylstilbestrol in utero (49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exposing female neonatal mice to the synthetic estrogen, ethinylestradiol, caused alteration in Cyst breakdown, oocyte survival and follicle development [13]. A combination of lignan, genistein and daidzein containing diet showed reduced serum estradiol levels in the pregnant rats as well as reduced anogenital distance in the newborn males [14]. While most of the researches focused on assessing the effects of isoflavones on postpubertal parameters, the researches which assess the effects of isoflavones on prepubertal parameters have not been fully demonstrated [15].…”
Section: Introductionmentioning
confidence: 99%